The fastest girl on Earth! : meet Kitty O'Neil, daredevil driver! - Robbins, Dean, 1957- (Alfred A. Knopf, 2021)
A picture book biography follows the life of Kitty O'Neil, the stuntwoman and racecar driver who broke the women's land speed record, becoming a hero to fans everywhere.